PGE2 transiently enhances DC expression of CCR7 but inhibits the ability of DCs to produce CCL19 and attract naive T cells - Muthuswamy, Ravikumar; Mueller-Berghaus, Jan; Haberkorn, Uwe; Reinhart, Todd A.; Schadendorf, Dirk; Kalinski, Pawel (Blood, 2010)
Prostaglandin E2 (PGE2) is an inflammatory mediator often used to increase CCR7 expression in the dendritic cells (DCs) used as cancer vaccines and to enhance their responsiveness to lymph node-associated chemokines. Here, we show that high surface expression of CCR7 on PGE2-matured DCs is associated with their suppressed production of the endogenous CCR7 ligand, CCL19, and is reversible by exogenous CCL19. In contrast to the PGE2-matured DCs, DCs matured in the presence of toll-like receptor (TLR) ligands and interferons produce high levels of both CCL19 and CCR7 mRNA/protein, but show selectively reduced expression of surface CCR7, which is compensated after DC removal from the CCL19-rich maturation environment. In accordance with these findings, PGE2-matured DCs show significantly higher in vitro migratory responsiveness to lymph node-associated chemokines directly after DC generation, but not after additional short-term culture in vitro, nor in vivo in patients injected with 111indium-labeled DCs. The differences in CCL19-producing ability imprinted during DC maturation result in their different abilities to attract CCR7+ naive T cells. Our data help to explain the impact of PGE2 on CCR7 expression in maturing DCs and demonstrate a novel mechanism of regulatory activity of PGE2, mediated by the inhibition of DCs ability to attract naive T cells.
Im Titel ist die Zahl "2" nach "PGE" tiefgestellt
Gesehen am 17.05.2023